The Philosophy of Humor Yearbook (De Gruyter, 2020)
The Philosophy of Humor Yearbook covers the various intersections of philosophy with humor (and laughter, irony, and the comical), historically and contemporarily, descriptively and prescriptively, seriously and jocularly. It welcomes excellent academic papers of both the analytic and continental traditions, reviews of relevant books, announcements of forthcoming events, and a section dedicated to humorous short papers on philosophical topics.